EVALUASI FASILITAS PENDUKUNG KEGIATAN TREKKING DIGUNUNG TALANG JALUR VIA AIA BATUMBUK - Dini Gusrianti; Andri Gemaini; Hastria Effendi; Alimuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the existence of several problems related to the supporting facilities for trekking activities on the Mount Talang hiking trail via Aia Batumbuk, including limited sanitation facilities, inadequate trail signage, and suboptimal facility maintenance. These conditions may affect the comfort, safety, and satisfaction of hikers during trekking activities. This study aimed to evaluate the supporting facilities for trekking activities in terms of availability, feasibility, accessibility, and maintenance. This research employed a quantitative descriptive method with a survey approach. The population consisted of all hikers who used the Mount Talang hiking trail via Aia Batumbuk, while the sample comprised 90 respondents selected through accidental sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics through percentage and mean calculations. The results showed that the overall evaluation of supporting facilities for trekking activities on the Mount Talang hiking trail via Aia Batumbuk achieved an average score of 61.58%, which falls into the good category. Specifically, the availability aspect scored 62.66%, feasibility 62.67%, accessibility 60.28%, and maintenance 59.65%. These findings indicate that the existing facilities are generally capable of supporting trekking activities adequately. However, improvements are still needed, particularly in maintenance, cleanliness, sanitation, and the provision of more accessible facilities to enhance service quality, safety, and visitor comfort in a sustainable manner.